Pemasaran Perumahan PT. Permata Indah Bersinar Menggunakan E- CRM Berbasis WEB - Noni Wahyuni; Mohd Siddik; Ruri Ashari Dalimunthe (Media Aplikom, 2020)
Quality of service at PT. Permata Indah Bersinar is still ineffective and not maximized. Because this company does not have a web-based housing marketing information system. This company also has not implemented a Customer Relationship Management strategy. In this research, the system created is a web-based housing marketing information system. With this system, companies will find it easier to disseminate information about their housing, consumers will also find it easier to get information without having to come directly to the marketing office. This system also implements Customer Relationship Management (CRM), so that consumers can ask and answer questions about housing through this website. By utilizing a housing marketing information system using web-based Customer Relationship Management (CRM), as an effort to improve service quality and increase customer satisfaction and maintain relationships between companies and consumers.